2019
DOI: 10.21608/ajas.2019.33488
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield of Some Jew's Mallow (Corchorus olitorius L.) Ecotypes as Affected by Planting Dates and Foliar Application of Gibberellic and Humic Acids

Abstract: A Field experiment was conducted in 2015 and 2016 cropping seasons at the Vegetable Crops Research Station, Faculty of Agriculture, Assiut University, to study the response of three Jew's Mallow Ecotypess (Assiut, Eskandarany and Aswan) to planting dates and foliar application of Gibberellic acid (GA3) and Humic acids (HA) treatments. The Jew's Mallow ecotypes were planted on 15 th Feb. and 15 th Oct. in both cropping seasons and subjected to three foliar applications of 0.25mg.l -1 GA 3 (T1), 0.5mg.l -1 HA (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Figure 1 displays the primary significance of the nutrient composition and estimated energy value, presented in terms of dry weight. The obtained results show that mallow has a high content of protein, carbohydrate, fat, and ash (20.22, 57.00, 2.86 and 17.84%) in dried stems compared to dried leaves, which ranged between 10.44 and 36.73% for protein, 46.07% for carbohydrate, 1.7 for fat and 7 and 16.13% for ash [ 31 , 32 , 33 ]. Fat was the least prevalent, with a macronutrient abundance of less than 3%.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1 displays the primary significance of the nutrient composition and estimated energy value, presented in terms of dry weight. The obtained results show that mallow has a high content of protein, carbohydrate, fat, and ash (20.22, 57.00, 2.86 and 17.84%) in dried stems compared to dried leaves, which ranged between 10.44 and 36.73% for protein, 46.07% for carbohydrate, 1.7 for fat and 7 and 16.13% for ash [ 31 , 32 , 33 ]. Fat was the least prevalent, with a macronutrient abundance of less than 3%.…”
Section: Resultsmentioning
confidence: 99%
“…The mallow (molokhia) plants (Corchorus olitorius L.), also known as Jew's mallow, wild okra, jute mallow, or tossa jute, are primarily herbaceous perennials from edible leafy vegetables or fiber crop in the Malvaceae family and present naturally in the Mediterranean (Cagirgan et al, 2014;Abdel-Razek et al, 2022). With a 2.45tons/ha productivity, Egypt's 887 hectares of jute mallow farming produced about 2173 tonnes of output (Haridy et al, 2019). Studies have shown that this plant plays a relevant role in maintaining human health, and the plant possesses a wide range of biological activities connected to its phytochemical composition (Moerman, 1996;Hussien et al, 2017;Abdel-Razek et al, 2022) as the leaves of C. olitorius include minerals, vitamins, and phenolic compounds that are abundant in plants (Schipper, 2000;Abdel-Razek et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…As well as, corchorus is an extremely popular Egyptian green vegetable. About 887 hectares is cultivated by Corchorus in Egypt and its total production is about 2173 tons (Abbas and Mousa, 2019). From the point of view of economic development and environmental protection, diverting organic wastes such as sewage sludge and crop residues to get values from them, such as energy production, is essential.…”
Section: -Introductionmentioning
confidence: 99%